How Work Environment, Work Satisfaction, Work Stress On The Turnover Intention Affect University Management - Soelton, Mochamad; Atnani, Muhammad (Jurnal Manajemen dan Bisnis Indonesia, 2018)
This study aims to determine the influence of Work Environment, Job Satisfaction and Job Stress on Turnover Intention at High School Technical Staff - PLN (STT - PLN) Jakarta. Technique of collecting data in form of questionnaire by using ordinal scale. This research was conducted on 50 respondents by using quantitative descriptive approach and hypothesis testing. For that, the method of data analysis used is statistical analysis in the form of multiple linear regression test. The results of this study show that partially and simultaneously, work environment variables, job satisfaction and work stress affect the Turnover Intention on High School Technical Staff - PLN (STT - PLN) Jakarta. Therefore the test result of this research states that there is simultaneous influence between work environment variable, Job Satisfaction and Working Stress on Turnover Intention on High School Technical Staff - PLN (STT - PLN) Jakarta.   Keywords: Work Environment, Job Satisfaction, Job Stress, Employee Turnover Intention